2010
DOI: 10.1111/j.1440-1819.2010.02077.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the processing of visual information from non‐verbal communications

Abstract: Aims: This paper examines the relationship between observational behavior and the observers' result assumptions, using a contained diagram that includes significant non-verbal information, such as gestures. The ability of care workers to assess a patient's mental status on the basis of nonverbal information would be considered an important skill necessary to understanding patient condition. Methods:One hundred and eleven subjects were asked to take a test exploring two types of psychological status, and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The results of the present study show that people with higher scores on openness traits returned their attention to the hazardous areas of scenes more frequently than people with lower scores on openness personality traits, perhaps suggesting that individuals who scored higher on openness actively sought information in the surrounding environment by processing the cues longer and in a more in-depth manner. This finding is in line with the findings of Matsumoto et al (2010) and Rauthmann et al (2012), which indicated that highly open individuals allocate more attention and deeper processing to the scene to obtain information from the hazardous stimulus. The current results might also reasonably be viewed from the standpoint of how the personal attribute of openness relates to providing a balance between focusing and distributing attention (i.e., the balance between fixation and run count).…”
Section: Openness To Experiencesupporting
confidence: 91%
“…The results of the present study show that people with higher scores on openness traits returned their attention to the hazardous areas of scenes more frequently than people with lower scores on openness personality traits, perhaps suggesting that individuals who scored higher on openness actively sought information in the surrounding environment by processing the cues longer and in a more in-depth manner. This finding is in line with the findings of Matsumoto et al (2010) and Rauthmann et al (2012), which indicated that highly open individuals allocate more attention and deeper processing to the scene to obtain information from the hazardous stimulus. The current results might also reasonably be viewed from the standpoint of how the personal attribute of openness relates to providing a balance between focusing and distributing attention (i.e., the balance between fixation and run count).…”
Section: Openness To Experiencesupporting
confidence: 91%
“…Twelve studies applied eye‐tracking to explore nursing students’ visual attention among different tasks. Eye‐tracking was used to assess the effect of communication training (Anbro et al., 2020 ), clinical bioethics decision‐making of nursing students (Fernandes et al., 2017 ), students’ visual behaviours and cognition engagement in simulated/virtual reality teaching (Amster et al., 2015 ; Dubovi, 2022 ; Groepel et al., 2022 ), factors influencing visual processing of non‐verbal communication (Matsumoto et al., 2010 ), communication skills training (Kobayashi et al., 2022 ), predict students’ self‐confidence (Vatral et al., 2023 ), students’ management of and response to interruptions (Vital & Nathanson, 2023 ), feasibility of eye‐tracking in simulated teaching, and the role of different visual interfaces in virtual teaching (Pence et al., 2014 ) as a method of feedback during students’ learning (Browning et al., 2016 ; O'Meara et al., 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies included nursing students as participants. Nineteen studies included not only nurses and nursing students, but also participants outside of these two, involving doctors (Broadbent et al., 2014 ; Chen & Law, 2023 ; Cui et al., 2022 ; Fogarasi et al., 2010 ; Law & Schmolzer, 2020 ; Valek et al., 2022 ), other medical students (Anbro et al., 2020 ; Browning et al., 2016 ; Groepel et al., 2022 ; Matsumoto et al., 2010 ; O'Meara et al., 2015 ; Wagner et al., 2022 ), technical associates & emergency service associates (Henneman et al., 2010 ), respiratory therapists (Chen & Law, 2023 ; Law et al., 2018 ; Law & Schmolzer, 2020 ), administrators (Cui et al., 2022 ). See Appendix S3 – population for details.…”
Section: Resultsmentioning
confidence: 99%
“…suggested that individual differences in personality such as anxiety (Paulitzki, Risko, Oakman, & Stolz, 2008) or loneliness (Wilkowski, Robinson, & Friesen, 2009) influence various forms of attention (e.g., task switching or gazetriggered orienting; see also Kaspar & König, 2012, for a review). With regard to the Big Five personality traits, participants with higher levels of openness showed increased durations of fixations to the eyes of an individual who sat opposite the participants (Matsumoto, Shibata, Seiji, Mori, & Shioe, 2010). According to the authors, a possible explanation may be that individuals who show higher levels of openness attempt to obtain information from the other person.…”
Section: Introductionmentioning
confidence: 98%